Central obesity and cardiovascular outcomes in patients with acute coronary syndrome: observations from the MERLIN-TIMI 36 trial. Issue 21 (23rd August 2011) - Kadakia, Mitul B; Fox, Caroline S; Scirica, Benjamin M; Murphy, Sabina A; Bonaca, Marc P; Morrow, David A
Abstract : Objective: Despite the association of obesity with incident cardiovascular disease, obese patients with acute coronary syndrome (ACS) appear to have more favourable short-term outcomes. A study was undertaken to determine whether this 'obesity paradox' persists in the long term and to examine the specific relationship of central obesity with outcomes after ACS. Methods: The relationship was investigated between two measures of obesity—body mass index (BMI) and waist circumference (WC)—and 30-day and 1-year outcomes after ACS. 6560 patients with non-ST elevation ACS in the MERLIN-TIMI 36 trial were followed for 1 year. Patients were stratified into three BMI groups (<25, 25–30, ≥30 kg/m 2 ) and gender-specific tertiles of WC. The primary endpoint was cardiovascular death, myocardial infarction or recurrent ischaemia. Results: Patients with BMI ≥30 kg/m 2 had a significantly lower risk of the primary endpoint than those with BMI <25 kg/m 2 (HR 0.64; 95% CI 0.51 to 0.81, p<0.0001) at 30 days. However, after the 30-day acute phase, landmark analysis from 30 days to 1 year showed no difference in risk between BMI groups (HR 1.09; 95% CI 0.92 to 1.29, p=0.34). WC tertiles demonstrated a similar relationship. When BMI groups were stratified by WC there was a trend towards more adverse outcomes in higher WC groups among those in lower BMI groups. The group with the lowest BMI and highest WC had the highest risk (HR 2.8; 95% CI 0.93 to 8.3; p=0.067). Conclusions: Obesity is associated with more favourable short-term outcomes after ACS. However, in the longer term the obesity paradox is no longer present and may reverse. Those with WC out of proportion to BMI suggestive of significant central adiposity may be at highest risk following ACS.